Morphometry of Sceloporus variabilis (Wiegmann 1834; Sauria: Phrynosomatidae) in three ecosystems of Veracruz, Mexico - Montiel-Martínez, Roberto Carlos; Serna-Lagunes, Ricardo; Torres-Cantú, Gerardo Benjamín; Mora-Collado, Norma; Andrés-Meza, Pablo; Ávila-Nájera, Dulce María; Hernández-Salinas, Gregorio (Ecosistemas y Recursos Agropecuarios, 2023)
Linear and geometric morphometry are tools that evaluate the morphological variation of the individuals of a species depending on the environment where their populations live. The objective of the study was to evaluate themorphology of three populations of Sceloporus variabilis in three ecosystems in central Veracruz, Mexico using linear and geometric morphometry. Collections of S. variabilis specimens were carried out in three ecosystems: high evergreenforest (SAP), subevergreen medium forest (SMSP), and cloud forest (BMM) and 16 landmark and 10 semilandmark were defined for analysis with geometric morphometry. Eight body measurements (snout-vent length, head length, head width, head height, snout length, distance between nostrils, body width and length) for analysis with linear morphometry, and their average values they were correlated with the environmental variables (temperature and average annual precipitation) ofeach collection location, in order to evaluate the response of the body structure with respect to environmental variation in the study ecosystems. The results indicate that the S. variabilis populations presented a similarity between the morphological characters evaluated with both geometric and linear morphometry, this meansthat the phenotype of S. variabilis individuals is similar, regardless of ecosystem conditions.
Keywords: pink-bellied spiny lizard; morphology; geometric morphometry; lineal morphometry